Mid-trimester spontaneous rupture of a bicornuate uterus: A case report - Heba Abu Saleem; Yara Edweidar; Mutaz Abu Salim; Ismaiel Abu Mahfouz (Elsevier, 2023)
Bicornuate uterus (BU) is a rare congenital anomaly that may present with various obstetric complications, and very rarely may be a risk factor for uterine rupture, even of an unscarred uterus.A 21-year-old primigravida woman, at 19 weeks and 5 days of gestation, presented with severe abdominal pain and features of hypovolemic shock. Urgent laparotomy showed a large hemoperitoneum, a ruptured left horn of a BU and a dead fetus in the abdominal cavity. Excision of the ruptured left horn was performed and the uterine defect was sutured. Postoperative recovery was uneventful. Bicornuate uterus is a rare uterine anomaly and is associated with various obstetric complications at different gestational ages. Ruptured uterus should be considered in the differential diagnoses of acute abdominal pain and a picture of hypovolemia in women with mid-trimester pregnancies.